Penerapan Argumentasi dan Bahan Ajar dalam Meningkatkan Pemahaman Materi Biologi Mahasiswa - Kencanawati, Indah; Siregar, Anggi Desviana; Hardiyanto, Toni; Purnawati, Wilda (Pedagogi Hayati, 2023)
Scientific argumentation aimed at reaching a rational perspective on science, scientific concepts, or elements within a scientific procedure. This study is experimental research employing a pretest-posttest control group design. The research was conducted with a population of 44 fifth-semester students majoring in biology education. The sample selection was performed using random sampling, consisting of two classes (experimental and control), each comprising 22 students. Data for the research were collected through pretests and posttests, which included 10 questions with five argumentation indicators via the minimum structure essay test. The research findings demonstrated an enhancement in students' ability to articulate their comprehension of the material when utilizing teaching materials compared to those who did not. As a result, it is recommended that the incorporation of teaching materials into the learning process be implemented in various other courses to foster the development of argumentation skills, including the presentation of claims, data, warrants, backing, and effective rebuttals in the learning process.